A Trial of Telephone Support Services to Prevent Further Intimate Partner Violence. (December 2015) - Stevens, Jack; Scribano, Philip V.; Marshall, Jessica; Nadkarni, Radha; Hayes, John; Kelleher, Kelly J.
We conducted a randomized-controlled trial of telephone support services (TSS) versus enhanced usual care (EUC) for women who had reported intimate partner violence (IPV) within the past year during a visit to a pediatric emergency department. TSS nurse interventionists identified appropriate referrals to community programs, helped participants by problem-solving barriers to obtaining these local services, and provided social support. Three hundred women, ages 18 years and above were recruited. The TSS and EUC groups did not differ on any outcome variable, including IPV victimization, feelings of chronic vulnerability to a perpetrator, depressive symptoms, and posttraumatic stress disorder symptoms.